2018
DOI: 10.1017/wsc.2018.52
|View full text |Cite
|
Sign up to set email alerts
|

Weed Seedbank and Weed Biomass Dynamics in a Long-Term Organic Vegetable Cropping Systems Experiment

Abstract: Most previous research on changes in weed abundance and community composition in cropping systems has focused on field crops. The study presented here examined changes in the weed seedbank and aboveground biomass in four organic vegetable cropping systems over a 10-yr period. The systems included an Intensive system with six crops per 4-yr rotation, an Intermediate system with one cash crop per year, a Bio-extensive system with alternating cash crop and tilled fallow years plus prevention of seed rain, and a R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…Agronomic practices can affect the weed flora and species composition of the weed community and soil seed bank in arable fields [7]. Crop rotation [8,9], fertilization [10][11][12][13], tillage [14][15][16], and crop residue retention [17][18][19] are effective measures to control weeds. No-till has been widely accepted in recent decades for many environmental benefits, such as reducing run-off, improving nutrient cycling, reducing soil degradation, decreasing water and soil pollution, and enhancing the activities of soil biota [20].…”
Section: Introductionmentioning
confidence: 99%
“…Agronomic practices can affect the weed flora and species composition of the weed community and soil seed bank in arable fields [7]. Crop rotation [8,9], fertilization [10][11][12][13], tillage [14][15][16], and crop residue retention [17][18][19] are effective measures to control weeds. No-till has been widely accepted in recent decades for many environmental benefits, such as reducing run-off, improving nutrient cycling, reducing soil degradation, decreasing water and soil pollution, and enhancing the activities of soil biota [20].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, fields may have weed communities dominated by species with similar phenology, reflecting the history of management (Ryan et al, 2010). For example, an organic vegetable rotation and a conventional corn and alfalfa rotation resulted in two different weed communities with very different phenology (Mohler et al, 2018). Likewise, corn and soybean are more conducive to summer annual broadleaf weed emergence than wheat and alfalfa (Goplen et al, 2017).…”
Section: Management Of Multiple Problem Weedsmentioning
confidence: 99%
“…Although the FSP experiment included only agronomic crops, rotations including short-season vegetable crops have been shown to impose even more restrictive filters by imposing tillage at various intervals throughout the growing season. This interrupts the life cycle of summer annual species requiring a full season for reproduction in favor of generalist species with more flexible emergence and early reproductive traits (Mohler et al 2018). There is currently a need for greater vegetable and lower commodity crop production to meet world dietary requirements (KC et al 2018) and the proximity of population centers to agricultural production fields in the mid-Atlantic area would facilitate delivery of more nutritionally balanced products.…”
Section: Management Implicationsmentioning
confidence: 99%
“…Fried et al (2008) suggest that a complex rotation with a complex array of crop perations would aid weed control by dampening populations of dominant noxious species and would be more favorable to species adapted to a range of cropping conditions, resulting in weed communities rich in generalist species. Mohler et al (2018) showed that vegetable crop rotations that employ multiple, appropriately timed tillage operations deplete the seedbanks of weed species having full-season reproductive requirements in favor of species with shorter reproductive cycles.…”
Section: Introductionmentioning
confidence: 99%